Game of Zones: how actin-binding proteins organize muscle contraction. Issue 2 (2nd April 2016) - Butkevich, Eugenia; Klopfenstein, Dieter R.; Schmidt, Christoph F.
ABSTRACT: Locomotion of C. elegans requires coordinated, efficient transmission of forces generated on the molecular scale by myosin and actin filaments in myocytes to dense bodies and the hypodermis and cuticle enveloping body wall muscles. The complex organization of the acto-myosin scaffold with its accessory proteins provides a fine-tuned machinery regulated by effectors that guarantees that sarcomere units undergo controlled, reversible cycles of contraction and relaxation. Actin filaments in sarcomeres dynamically undergo polymerization and depolymerization. In a recent study, the actin-binding protein DBN-1, the C. elegans ortholog of human drebrin and drebrin-like proteins, was discovered to stabilize actin in muscle cells. DBN-1 reversibly changes location between actin filaments and myosin-rich regions during muscle contraction. Mutations in DBN-1 result in mislocalization of other actin-binding proteins. Here we discuss implications of this finding for the regulation of sarcomere actin stability and the organization of other actin-binding proteins.